Introducing Volcanica: The first diamond open-access journal for volcanology - Farquharson, Jamie Ian; Wadsworth, Fabian B (Volcanica, 2018)
Welcome to Volcanica’s first issue! Our community of editors and Volcanica supporters are excited to present you with our inaugural issue of peer-reviewed volcano research. This editorial accompanies the first issue of Volcanica so that we can provide you with some background to the Volcanica initiative, explain some of the evidence-based motivation for starting a new journal, and explore ways in which we can improve universal access to published research. We discuss our model of "diamond open access", which is entirely free for authors to publish and free for everyone to read. We will explain how this model is possible and state explicitly the challenges related to how this project can be sustainable and scalable. Finally, we will signpost the information you may need to publish with Volcanica as we continue to grow.